Analysis of the wake mechanism in external flow around tandem bluff bodies with different aspect ratios - Abbasi, Waqas Sarwar; Ehsan, Muhammad; Rahman, Hamid; Uddin, Zia; Hassan, Mohammad Mehedi; Saleem, Kashif (Frontiers in Mechanical Engineering, 2024)
The interaction mechanism of external flow with two inline rectangular cylinders having different aspect ratios under the impact of gap spacing (G) is studied in this work. The gap spacing among cylinders is varied from 0.25 to 20 times size of cylinder. Both the cylinders are vertically mounted and the first cylinder has higher aspect ratio than the second one. The results reveal five distinct flow patterns under influence of G: Single Slender Body, Shear Layer Reattachment, Intermittent Shedding, Binary Vortex Street and Single Row Vortex Street. The mean pressure on both cylinders is found to be varying due to change in flow patterns. Both cylinders bear same shedding frequency but have difference in pressure variations. The second cylinder placed in the wake of first one experiences negative average drag force for some spacing values while the first cylinder has positive average drag values for all chosen G. Due to the change in flow pattern from shear layer reattachment to intermittent shedding flow, the negative drag force on second cylinder jumped to positive one. It is also observed that the rms values of drag and lift force coefficients as well as their amplitudes for second cylinder are mostly higher than corresponding values for first cylinder at all selected G. This study reveals that G = 4 and 8 are the critical gap spacing values due to sudden changes in fluid force parameters.